Cost-effectiveness of rivaroxaban versus warfarin for treatment of nonvalvular atrial fibrillation in patients with worsening renal function. (1st May 2019) - Salcedo, Jonathan; Hay, Joel W.; Lam, Jenny
Abstract: Background: Nonvalvular atrial fibrillation (NVAF) is highly prevalent and increases the risks of cardiovascular events. In a recent subgroup analysis, treatment response was shown to vary for patients exhibiting worsening renal function (WRF) on-treatment. It is important to understand the cost-effectiveness of novel oral anticoagulant (NOAC) use in this population. Methods: A cost-effectiveness analysis (CEA) was conducted using a Markov model to determine whether NOAC rivaroxaban treatment is cost-effective relative to warfarin in NVAF patients with on-treatment WRF. Input parameters were sourced from clinical literature including a multicenter clinical trial and subgroup analysis. We studied elderly US male patients at increased risk for stroke (CHADS2 score ≥ 2) undergoing treatment for NVAF and exhibiting WRF. Main outcome measures included total healthcare costs in 2017 US dollars (societal perspective), total quality-adjusted life years (QALYs), incremental cost-effectiveness ratio (ICER), and incremental net monetary benefits (INMB) per-patient. Results: The remaining lifetime use of rivaroxaban is associated with 5.69 QALYs at a cost of $66, 075 per patient, while warfarin produced 5.22 QALYs with costs of $78, 504 per patient. At a willingness-to-pay (WTP) of $150, 000 per QALY, incremental net monetary benefits (INMB) per patient are $83, 590. In our population, treatment with warfarin was dominated by rivaroxaban in 99.4% of 10, 000 simulations. Conclusions: Rivaroxaban is likely a dominant treatment over warfarin in elderly US male NVAF patients exhibiting WRF, providing increased QALYs at a decreased overall cost. Application of these findings may require healthcare providers to predict which patients are likely to exhibit WRF. Highlights: Rivaroxaban is dominant to warfarin for NVAF with WRF in elderly US males. At $150, 000 per year of perfect health, monetary benefits are $83, 590 per patient. Rivaroxaban provides greater benefit at a lower cost than warfarin. Rivaroxaban may be an attractive alternative to warfarin in this population.